Pengembangan Sistem Informasi Perpustakaan Sekolah Berbasis Web - Granita, Savira; Rohmaniyah, Siti; Gautama, Tio; Yulianti, Yulianti (Program Studi Teknik Informatika Universitas Pamulang, 2020)
The school library is a means for teachers and students to find information. The school library provides books or reading materials that can support the learning process. The focus of this research is to develop the information system contained in the school library. Many school libraries still collect data in the conventional way, such as handwritten using a ledger or using excel. The development of this school library system will use the website as a means to process data. The data that has been created will be entered into the data storage using the MySQL application as the database. This research planning uses the SDLC method with the waterfall model. The waterfall model is used because it is considered more efficient in developing school libraries. There are two entities that can use this website, namely library officers and members. Library officers can use the web to process data on book procurement, book borrowing transactions and viewing library reports. Meanwhile, members can fill in the guest book every time they visit the school library and also do book searches. Thus, the school library information system can facilitate the data processing. Book lending and borrowing transactions will also be more efficient and errors in data processing can be reduced.